2014
DOI: 10.1093/mnras/stu1251
|View full text |Cite
|
Sign up to set email alerts
|

Parametric studies of cosmic ray acceleration in supernova remnants

Abstract: We present a library of numerical models of cosmic-ray accelerating supernova remnants (SNRs) evolving through a homogeneous ambient medium. We analyze distributions of the different energy components and diffusive shock acceleration timescales for the models in various conditions. The library comprises a variety of SNR evolutionary scenarios and is used to map remnants with sufficiently known properties. This mapping constrains the respective ambient medium properties and the acceleration efficiency. Employin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
(115 reference statements)
0
12
0
Order By: Relevance
“…The CR injection momentum parameter ξ can typically be in the range 3.0−4.5, where high values of ξ ≥ 4.0 correspond almost to the test-particle regime and low values of ξ ≤ 3.5 imply efficient DSA (Kosenko et al 2014). We adopt the common value ξ = 3.4, but also run simulations with ξ = 3.3 and ξ = 3.2 in order to study the sensitivity of the calculations to the value of this parameter.…”
Section: Resultsmentioning
confidence: 99%
“…The CR injection momentum parameter ξ can typically be in the range 3.0−4.5, where high values of ξ ≥ 4.0 correspond almost to the test-particle regime and low values of ξ ≤ 3.5 imply efficient DSA (Kosenko et al 2014). We adopt the common value ξ = 3.4, but also run simulations with ξ = 3.3 and ξ = 3.2 in order to study the sensitivity of the calculations to the value of this parameter.…”
Section: Resultsmentioning
confidence: 99%
“…Note, that the oxygen abundance derived from the spectral fitting is about four times higher than in SNR 0509-67.5. The parametric studies (Kosenko, Ferrand & Decourchelle 2014) give n 0 = (0.5 − 1.0) cm −3 (for an explosion energy of 10 51 erg) and the light echo measurements of Rest et al (2005) indicate an age of 600 ± 200 yr.…”
Section: Oxygen In Supernova Remnants In the Large Magellanic Cloudmentioning
confidence: 98%
“…In order to confront the data with the models it is essential to know the dynamical properties and evolutionary stages of the remnants with sufficient accuracy. The analysis of SNR 0509-67.5 data reported by Kosenko et al (2008) gives an ISM density of n 0 = (0.4 − 0.6) cm −3 , Warren & Hughes (2004) measured n 0 = 1 Version 12.7.1 0.05 cm −3 , and an SNR parametric analysis reported in Kosenko, Ferrand & Decourchelle (2014) constrains n 0 to (0.1 − 0.3) cm −3 (for an SN explosion of 10 51 erg). Using light echo measurements Rest et al (2005) limited the age of SNR 0509-67.5 to 400 ± 120 yr. Measurements of Ghavamian et al (2007) give an age in the range 300 − 600 yr. Badenes et al (2008) suggested that the remnant originated 400 years ago and expands through an ISM with 0.4 cm −3 .…”
Section: Oxygen In Supernova Remnants In the Large Magellanic Cloudmentioning
confidence: 98%
“…For the remnants 0509-67.5 and 0519-69.0, the same method constrains the neutral hydrogen fraction in the surrounding ISM to >40%. The best-fitting ambient densities can be found from comparing the present size and ionization state of the remnant with hydrodynamical models: recently, Kosenko et al (2014) found n 0 = 0.1-0.3cm −3 for 0509-67.5, and n 0 = 1.0-2.0cm −3 for 0519-69.0, although Kosenko et al (2010) report densities as high as 2.4cm −3 . As a conservative estimate, we adopt 0.3cm −3 and 2.4cm −3 as our fiducial ISM densities for 0509-67.5 and 0519-69.0 respectively.…”
Section: Magellanic Supernova Remnantsmentioning
confidence: 99%